2001
DOI: 10.1128/jvi.75.2.952-960.2001
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus A9 VP1 Mutants with Enhanced or Hindered A Particle Formation and Decreased Infectivity

Abstract: We have studied coxsackievirus A9 (CAV9) mutants that each have a single amino acid substitution in the conserved 29-PALTAVETGHT-39 motif of VP1 and a reduced capacity to produce infectious progeny virus. After uncoating, all steps in the infection cycle occurred according to the same kinetics as and similar efficiency to the wild-type virus. However, the particle/infectious unit ratio in the progeny was significantly increased. The differences were apparently due to altered stability of the capsid: there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…The basic, positively charged lysine at positon 244 was replaced with an acidic, negatively charged glutamic acid. H37R was a switch between two basic amino acids located in a conserved hook region on the interior portion of VP1 (24) (Fig. 3B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic, positively charged lysine at positon 244 was replaced with an acidic, negatively charged glutamic acid. H37R was a switch between two basic amino acids located in a conserved hook region on the interior portion of VP1 (24) (Fig. 3B).…”
Section: Resultsmentioning
confidence: 99%
“…The H37R VP1 mutation resides in a conserved hook region that stabilizes the capsid into its mature form and increases the thermal energy required for uncoating (24). This mutation has not been found to help compensate for mutations at position 244 in previous studies.…”
Section: Figmentioning
confidence: 98%
“…The inter-pentameric interface residues and their associated interactions are responsible for stabilisation and infectivity of the virion [21,28]; however, experimental studies on the molecular interactions relating to capsid assembly, disassembly, and stability are still very limited. Furthermore, mutations nearby the FMDV interfaces can affect conformational stability [29][30][31][32]. We recently showed that using reverse genetic approaches, we could improve stability by introducing stabilising mutations into a SAT2 infectious clone and recovering stabilised viruses [20].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous analysis, we provided evidence that in FMDV, most residues at the capsid interpentamer interfaces, and their interactions, are important for the infectivity, and stability, of the virion (35). In addition, a few mutations outside these interfaces have been shown to have an effect on the conformational stability of picornaviruses, including FMDV (2,24,50,55). Four (nearly half) of the mutations in the capsid of FMDV R100 involve identical clusters of residues that surround the pores at each capsid fivefold symmetry axis (16) (Fig.…”
mentioning
confidence: 99%